The Effect of pncA Gene Mutation of Mycobacterium Tuberculosis to Transaminase and Uric Acid Serum in MDR TB Patient - Yeni Vera; Bintang YM Sinaga; Dedi Ardinata; Yahwardiah Siregar (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Bacground: The common side effects of PZA treatment is the occurrence of hepatotoxicity and blocking the secretion of uric acid. This study aims to determine the effect of the pncA gene mutation of Mycobacterium tuberculosis to serum transaminase and serum uric acid in patients with MDR TB who had receive therapy with PZA. Methods: Quasi-experimental test was conducted at MDR TB polyclinic in H. Adam Malik Medan Hospital of 25 patients with MDR TB. Mutations of genes was assessed by PCR-RFLP method and data of serum transaminase and serum uric acid retrieved from the medical records, between February until June 2015 Result: Thirtysix percent pncA gene mutation founded. Significance statistic test between mutation of pncA gene and SGOT serum in baseline Vs 4 weeks (P=0,007), baseline Vs 8 weeks (P=0,023) and uric acid serum baseline Vs 4 weeks (P=0,011). No statistically difference in SGPT serum. No correlation between pncA gene (mutation and no mutation) with transaminase serum and uric acid serum. Conclusion: Transaminase serum and uric acid elevated in MDR TB patient with mutation in pncA gene.Mutation in pncA gene have a correlation with elevated SGOT serum compared between baseline, 4 and 8 weeks. No correlation between pncA gene mutation and SGPT. Mutation in pncA gene have a correlation with uric acid serum elevated in 4 weeks. No correlation between pncA gene (mutation and no mutation) with transaminase serum and uric acid serum elevated.